The Last Panda. - Schaller, George B. (University of Chicago Press, 1994)
Dependent on a shrinking supply of bamboo, hunted mercilessly for its pelt, and hostage to profiteering schemes once in captivity, the panda is on the brink of extinction. Here, acclaimed naturalist George Schaller uses his great evocative powers, and the insight gained by four and a half years in the forests of the Wolong and Tangjiahe panda reserves, to document the plight of these mysterious creatures and to awaken the human compassion urgently needed to save them.""No scientist is better at letting the rest of us in on just how the natural world works; no poet sees the world w.